An investigation of the attitudes and awareness of the risks associated with cannabis use in an Irish adolescent population. (24th May 2012) - Barrett, P; Bradley, C
Abstract : Introduction: Cannabis is the most widely used illicit drug in the developed world and its use has been associated with several adverse physical and mental health effects and negative social outcomes. Cannabis has the lowest initiation age of any drug, and an earlier age of first use of cannabis increases the risk of adverse effects and later use of hard drugs. Attitudes and perceived risk towards drugs have been regarded as strong influences in determining cannabis use, but there is relatively little research done to date on attitudes and awareness of teenagers of the risks of this drug. Aims: To investigate the attitudes of Irish adolescents towards the risks associated with cannabis use. To evaluate their awareness of its associations with adverse health and social outcomes. Methods: This was a descriptive, cross-sectional study using a structured, anonymous questionnaire. The study was undertaken in nine public and private secondary schools in Cork City and suburbs. Participating students were aged 15–18 years. Results: Of the 507 participating students, 39.3% reported previous cannabis use. Of those who had used cannabis, 33% reported using it more than 10 times in the past. There were significantly lower levels of perceived risk of cannabis among those who had used the drug compared with those who had not for all categories of social, physical and mental health risks (p<0.001). There was a good overall level of knowledge of the effects of cannabis, with a notable lack of awareness of the potential increased risk of schizophrenia. The majority of teenagers believe there is peer pressure on them to use cannabis (55.0%), but only a minority agree with legalisation (18.2%). Most teenagers (75.8%) believe that they are not given enough information about the drug. Conclusions: Cannabis use is extremely widespread among teenagers in Cork. There are relatively low levels of perceived risk of mental and physical health problems with the drug. There are important deficiencies in teenagers' knowledge, and more targeted information is required to address this.